2012
DOI: 10.1542/peds.2011-0813
|View full text |Cite
|
Sign up to set email alerts
|

Level of NICU Quality of Developmental Care and Neurobehavioral Performance in Very Preterm Infants

Abstract: Very preterm infant neurobehavior was associated with higher levels of developmental care both in ICC and in IPM, suggesting that these practices support better neurobehavioral stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
107
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(115 citation statements)
references
References 29 publications
3
107
0
2
Order By: Relevance
“…This is concurrent with other findings using the NNNS assessment, where different NNNS summary scores have been associated with unique and specific epigenetic patterning 10,11,13,41,42 or factors from the prenatal environment. [20][21][22][23][24][25][26][27] Quality of movement and infant attention were associated with methylation of genes involving neurological development and function, including neurotransmitter uptake, dopamine uptake involved in synaptic transmission, and dendritic spine organization. The placenta is an endocrine organ that expresses similar neuropeptides to the human brain, 43 and previous studies have identified associations between methylation of genes that are expressed within the human brain, such as the serotonin receptor HTR2A.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is concurrent with other findings using the NNNS assessment, where different NNNS summary scores have been associated with unique and specific epigenetic patterning 10,11,13,41,42 or factors from the prenatal environment. [20][21][22][23][24][25][26][27] Quality of movement and infant attention were associated with methylation of genes involving neurological development and function, including neurotransmitter uptake, dopamine uptake involved in synaptic transmission, and dendritic spine organization. The placenta is an endocrine organ that expresses similar neuropeptides to the human brain, 43 and previous studies have identified associations between methylation of genes that are expressed within the human brain, such as the serotonin receptor HTR2A.…”
Section: Discussionmentioning
confidence: 99%
“…16 This assessment has established validity in identifying high-risk infants and predicting later life health outcomes. [17][18][19][20][21][22][23][24][25][26][27][28] The cohort examined in this study represents a relatively healthy population, and the maternal environment experienced by these infants is likely similar to the population at large. These results suggest that there is an underlying level of variation in behavioral phenotypes as well as a level of epigenetic variation in the placenta of otherwise healthy infants, and that in some cases the variation in the placenta is related to the variation observed in neurobehavioral outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Better developmental care in the NICU (Neonatal Intensive Care Unit) improves developmental outcome on the NNNS in preterm infants when they are discharged from the hospital. 29 In addition, NNNS findings in preterm infants shortly before NICU discharge are more positive when there is more family centered care, developmental care and parent satisfaction and less maternal depression and parenting stress. 30 The NNNS may be useful in implementing developmental models of care in the NICU and identifying infants who may be at high risk for poor developmental outcome even without medical problems.…”
Section: Researchmentioning
confidence: 99%
“…During the period of hospitalization in the Neonatal Intensive Care Unit (NICU), neonates are exposed to numerous stressors, including painful stimuli, sleep disruption, excessive noise, high light levels, frequent handling associated with nursing procedures and maternal separation (2) . On average, they are subjected to 16 painful procedures per day, the majority of which occur without analgesia (3) , which highlights the need for changes in the practice of care to reduce stress and pain and to promote improved clinical and adequate neurobehavioral development for the neonates.…”
Section: Introductionmentioning
confidence: 99%